Skill Gap from Employers’ Evaluation: The Case of Graduates from Vietnam National University, Hanoi - Thi Quynh Lan, Mai (VNU Journal of Science: Education Research; Vol 34 No 2DO - 10.25073/2588-1159/vnuer.4137, 2018)
With globalization, the university-work transition has become increasingly challenging for graduates and employers. In the new context, the mission of university has shifted, and knowledge is no longer considered as singular [1]. The traditional role of universities in producing knowledge has changed to give more focus on the demands of society. The “codified knowledge” acquired from didactic teaching in universities can be at odds with the often “informal and tacit” knowledge required in the workplace. The development of information technology makes the nature of work changing very fast; graduates need to achieve attributes that help them not only do the work corresponding with their disciplines, but be able to learn new skills and new knowledge. This paper presents the primary results of a questionnaire survey among 25 employers of VNU School of Law’s graduates to explore employers’ evaluation of the employability of graduates from Vietnam National University Hanoi. Applying theories of graduate attributes [2], employability [3] and graduate transferable skills [4], [5], the survey explores the gap between university study and the requirements at the work market of graduates. This paper argues that there is considerable distance between university knowledge and skills and the nature of the work. Graduates lack transferable skills, those that allow them to acquire the necessary skills, to satisfy the requirements of the morden workplace, to transfer abstract cognitive skills. These skills are needed before the graduates enter the work market as the employers expect them to practice these skills competently at work. Although these skills can be generated through work, the employers do emphasise their importance for univesrity graduates. Therefore the university teaching and learning process should be reviewed and revised (if necessary) to develop these transferable skills during the time at the university.